ANALISIS KARAKTERISTIK TERMAL BIO OIL DAN BIO ARANG DENGAN PROSES PIROLISIS MENGGUNAKAN BAHAN BAKU KALIANDRA MERAH - Rouli Pasaribu, Viviany; A. Abdullah, Nasruddin; Bahri Widodo, Syamsul (JURUTERA - Jurnal Umum Teknik Terapan, 2025)
The global demand for fuel oil continues to rise, while petroleum reserves are steadily declining. As a response to this challenge, new and renewable energy sources (EBT) offer viable alternatives, minimizing environmental impact while ensuring long-term energy sustainability. Among these alternatives, bio-oil and biochar emerge as promising renewable energy sources. This study aims to analyze the thermal characteristics of bio-oil and biochar produced through pyrolysis using red calliandra wood as a feedstock. The pyrolysis process was conducted at varying temperatures of 300 °C, 400 °C, and 500 °C for 60 minutes. Results indicate that the optimal pyrolysis temperature is 500 °C, yielding biochar with the highest calorific value of 7,145 cal/g and bio-oil with a calorific value of 3,276 cal/g. Thermal analysis reveals significant activity at 283 °C, indicating the thermal decomposition of red calliandra biomass. Higher pyrolysis temperatures enhance biochar quality by reducing moisture and ash content while increasing fixed carbon concentration. The findings underscore the potential of red Calliandra wood as a renewable energy feedstock. This research contributes to the advancement of biomass-based energy technologies and presents opportunities for further optimization of the pyrolysis process. Given Indonesia’s abundant biomass resources, biochar offers a promising pathway for sustainable energy development.